Narrative Confetti - Subjects, Truth and Ethics - Stephen Webb (Social Work and Society, 2006)
Imagine three budding authors taking time off from their busy consultancy work, meeting for a coffee to discuss drafting a proposal for this book. Whilst the more experienced writer, is taking the lead, this is very much conceived as a joint project of equal partners. So the three of them sit down and begin the process of sorting and classifying a potential outline for the book proposal. They might even have struggled for a while with the notion that writing a book on rights and ethics under the auspices of a"care management" series is a bit of a contradiction in terms. Never mind. Ploughing on they consider the Heinemann format for these little books. Lashings of case studies, cartoon characters, bullet-point summaries, half-tone box inserts, diagrams that represent"real life" scenarios, mixing of font sizes etc.. Herein lays the typical postmodern hypertext marriage of high and low, iconic and textual, surface and depth (Harlow, 2003). So far so good. Next they begin to consider critical decisions about their various contributions, who will write what and how they will share the workload. After a successful meeting in which everyone is cheered by the prospect of such an exciting project, they go their separate ways, agreeing to exchange emails. On the way home, one author has the bright idea that diversity is really reducible to"three-world views". Stealing on the old German mandarin tradition of e"Weltanschauung" as a generative system for explaining historical and cultural continuity, s/he feels to have captured the organic unity of diversity in a nutshell. Enthused, s/he quickly texts the co-writers"had a great idea about how we can overcome the diversity problem". Later that night paging through a copy of Freedman and Combs's Narrative Therapy: The Social Construction of Preferred Realities, s/he is astonished to find they've developed a similar conceptual schema. Cryptomnesia, fate or chance?"Who knows, after all it only ever amounts to 'preferred realities' that we choose even though they are socially constructed for us", s/he muses.